HUBUNGAN PENGETAHUAN TENTANG BODY MECHANIC TERHADAP TINGKAT NYERI LOW BACK PAIN (LBP) PADA PETANI KELAPA SAWIT - Ispika Roma; Bayhakki Bayhakki; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Body mechanic is a coordinated and safe use of the body to produce movement and maintain balance during activity. One of the effects of a body mechanic error is the occurrence of LBP. LBP is pain that is felt in the lower back area, it can be local or radicular pain or both. This study aims to determine the relationship between knowledge about body mechanic and low back pain (LBP) of oil palm farmers. This study uses a quantitative correlation research design with cross sectional design. The sampling method uses purposive sampling with 64 respondents. The measuring instrument used in this study is a questionnaire and observation sheet to see the level of knowledge and pain scale. Analysis of the data used consisted of univariate analysis to determine frequency distribution and bivariate analysis to see the relationship between the 2 variables studied using Fisher's Exact test. The results showed that there was no relationship between knowledge about body mechanics on the incidence of low back pain (LBP) of oil palm farmers with p value (1,000)> ɑ (0.05). Based on the results of the study, it is expected that oil palm farmers can find out and apply the way to carry heavy objects on the right position in daily life.Keywords: Body mechanic, knowledge, low back pain